2015
DOI: 10.1007/s11056-015-9499-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of stored carbohydrates and nitrogen in the growth and stress tolerance of planted forest trees

Abstract: Plants store compounds that supplement external resources to maintain primary functions. We reviewed the role of stored non-structural carbohydrates (NSC) and nitrogen (N) in juvenile woody species for spring growth and cold and drought stress tolerance, which are crucial processes for early performance of forest plantations. Plant functional types differed in NSC and N partitioning and allocation to new growth. In general, however, new leaves/shoots were more enriched in remobilized resources than new fine ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 144 publications
(225 reference statements)
6
67
3
5
Order By: Relevance
“…Studies with Picea abies L. and Pinus pinea L. seedlings, using low and high fertilization rates, indicated that NSC contents were positively and negatively correlated with fertilization rates, respectively (Kaakinen et al 2004;Villar-Salvador et al 2013). Stored N and NSC are functional attributes, indicative of seedling quality and a substantive body of evidence in the literature concludes that over-fertilization retards N storage (Millard and Grelet 2010;Villar-Salvador et al 2015). These inconclusive NSC responses to nursery fertilization imply effects beyond N uptake and storage on carbon assimilation and sequestration.…”
Section: Impact Of Controlled Release Fertilizer Rate On Chinese Pinementioning
confidence: 99%
See 1 more Smart Citation
“…Studies with Picea abies L. and Pinus pinea L. seedlings, using low and high fertilization rates, indicated that NSC contents were positively and negatively correlated with fertilization rates, respectively (Kaakinen et al 2004;Villar-Salvador et al 2013). Stored N and NSC are functional attributes, indicative of seedling quality and a substantive body of evidence in the literature concludes that over-fertilization retards N storage (Millard and Grelet 2010;Villar-Salvador et al 2015). These inconclusive NSC responses to nursery fertilization imply effects beyond N uptake and storage on carbon assimilation and sequestration.…”
Section: Impact Of Controlled Release Fertilizer Rate On Chinese Pinementioning
confidence: 99%
“…Timmer's conceptual model for optimizing fertilization based on investigating the impact of fertilization rates on plant dry mass and mineral nutrient status has not been assessed yet for CRF. Measurements of non-structural carbohydrate (NSC) levels in seedlings also appear to be useful for evaluating nursery practices (Millar and Grelet 2010;Villar-Salvador et al 2015). The lack of research using a sufficiently broad range of CRF rates to cover nutrient deficiency to toxicity (Oliet et al 2004(Oliet et al , 2009Luis et al 2009;Dumorese et al 2011), hinders seedling nutrient optimization.…”
Section: Introductionmentioning
confidence: 99%
“…They discuss disturbance regimes in which restoration may benefit from artificial inoculation of nursery stock or introduction of ectomycorrhizae onto field sites, yet they also highlight the complexity of fully understanding this below-ground community and the challenges of artificially reintroducing a diverse ectomycorrhizal community across heavily disturbed landscapes. In another paper from an invited keynote presentation, Villar-Salvador et al (2015) traced the importance of stored non-structural carbohydrates and N in determining stress resistance of newly planted forest trees. Using a meta-analysis approach, they found distinctions among plant functional types in storage patterns of carbohydrates and N within plant tissues as well as their reallocation to support growth following transplant.…”
Section: The Role Of Genetics In Producing Resilient Ecosystemsmentioning
confidence: 99%
“…At the same time, increase in the amount of nitrogen in roots was about 5% (Coker 1984). In case of oak seedlings, the amount of nitrogen loss may be much greater than that in the pine, as in deciduous seedlings which loose leaves, the amount of nitrogen stored in the roots is considerably greater in comparison to coniferous seedlings (Villar-Salvador et al 2015).…”
Section: Discussionmentioning
confidence: 97%